Front Cover: Photochemical Synthesis of cis, trans, cis‐1, 2, 3, 4‐Tetrakis(diphenylphosphanyl)buta‐1, 3‐diene and Its Metal Coordination (Eur. J. Inorg. Chem. 46/2018). Issue 46 (30th November 2018) - Prock, Johannes; Ehrmann, Katharina; Viertl, Wolfgang; Pehn, Richard; Pann, Johann; Roithmeyer, Helena; Bendig, Marvin; Rodríguez Villalón, Alba; Kopacka, Holger; Dumfort, Alexander; Oberhauser, Werner; Clausing, Simon T.; et al.
Abstract : The Front Cover shows the important steps of the synthesis of dppbd. After the formation of the initial intermediate, comes the second and key step, which is a light induced pericyclic cycloaddition, immediately followed by a thermally induced ring opening reaction. The third step is the removal of platinum, which was used as a template. The last step shows two examples of the coordination of metal centers. In the background is an excitation/emission spectrum of a compound consisting of osmium and the title compound, demonstrating its application as a photosensitizer. More information can be found in theFull Paper by W. Oberhauser, G. Knör, P. Brüggeller et al. For more on the story behind the cover research, see theCover Profile .